Three hero stones in the premises of the Suswani Mata Temple Complex - Temples of India Project Team (Jio Institute, 2024)
Typically, the front side of the Hero stones depicts a hero riding on horseback, accompanied by a female figure standing in front of him with her hands folded in namaskar mudra (salutation gesture). The size of this depiction might vary on each stone, but they maintain stylistic similarity. Sometimes, these figures include inscriptions that provide details such as the person honoured by the hero stones and crucially, the date of its creation. The dates from legible inscriptions on the Hero stones are from 1500 VS onwards, placing them in the 15th-16th centuries CE.